2023
DOI: 10.3390/plants12193479
|View full text |Cite
|
Sign up to set email alerts
|

Wild-Grown Romanian Helleborus purpurascens Approach to Novel Chitosan Phyto-Nanocarriers—Metabolite Profile and Antioxidant Properties

Adina-Elena Segneanu,
Gabriela Vlase,
Titus Vlase
et al.

Abstract: The current nanomedicinal approach combines medicinal plants and nanotechnology to create new scaffolds with enhanced bioavailability, biodistribution and controlled release. In an innovative approach to herb encapsulation in nanosized chitosan matrices, wild-grown Romanian Helleborus purpurascens was used to prepare two new chitosan nanocarriers. The first carrier preparation involved the nanoencapsulation of hellebore in chitosan. The second carrier emerged from two distinct stages: hellebore-AgNPs phyto-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 169 publications
0
3
0
Order By: Relevance
“…The radical scavenging properties of the novel carrier system and herb sample were assessed according to the procedure described in our earlier publication [ 93 ]. The results were used to calculate and obtain the IC 50 (mg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…The radical scavenging properties of the novel carrier system and herb sample were assessed according to the procedure described in our earlier publication [ 93 ]. The results were used to calculate and obtain the IC 50 (mg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…The collective results of the antioxidant assays used in this study indicate that the new phyto-nanocarrier prepared has a very high antioxidant activity compared to the plant sample, considering the influence of the reaction parameters (molar ratio, solvent polarity, pH, temperature) such as and the modification of the structural properties (size particles, specific surface, etc.) occurring as a result of the employed experimental procedure [111,112]. Various studies reported that loading the zeolite pores with phytochemicals enhances in vivo biocompatibility and stability, as well as prolonged controlled release [18,19].…”
Section: Phosphomolybdate Assay (Total Antioxidant Capacity)mentioning
confidence: 99%
“…The total antioxidant capacity assay of SZ phyto-nanocarrier and ironwort sample was carried out according to phosphomolybdenum, a procedure described in our earlier publication [111]. The results are presented as µg/mL of ascorbic acid equivalents (AAE).…”
Section: Phosphomolybdate Assay (Total Antioxidant Capacity)mentioning
confidence: 99%